2016
DOI: 10.1128/jvi.00266-16
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-Cell Contact and Nectin-4 Govern Spread of Measles Virus from Primary Human Myeloid Cells to Primary Human Airway Epithelial Cells

Abstract: Measles is a highly contagious, acute viral illness. Immune cells within the airways are likely first targets of infection, and these cells traffic measles virus (MeV) to lymph nodes for amplification and subsequent systemic dissemination. Infected immune cells are thought to return MeV to the airways; however, the mechanisms responsible for virus transfer to pulmonary epithelial cells are poorly understood. To investigate this process, we collected blood from human donors and generated primary myeloid cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 45 publications
3
40
2
Order By: Relevance
“…Infected circulating immune cells subsequently spread the virus to epithelial cells via contact with nectin-4, which is expressed on the basolateral side of the apical junction complexes (18,19). Virus then invades the epithelium and, after replication in epithelial cells, is released into the upper respiratory tract, where it can be transmitted to the next host (20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Infected circulating immune cells subsequently spread the virus to epithelial cells via contact with nectin-4, which is expressed on the basolateral side of the apical junction complexes (18,19). Virus then invades the epithelium and, after replication in epithelial cells, is released into the upper respiratory tract, where it can be transmitted to the next host (20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…interaction energy models revealed that some gD may interact with nectin-3, and more importantly, with nectin-4, as this receptor showed the highest overall affinity with gD. Nectin-4 is known to be involved in cell entry mechanisms of paramyxoviruses (Mühlebach et al 2011;Noyce et al 2013;Delpeut et al 2014;Singh et al 2016),…”
Section: Discussionmentioning
confidence: 99%
“…Those two modes of dissemination are 1) diffusion of cell-free virus and 2) cell-to-cell spread. Several enveloped viruses including flavivirus, herpesviruses, paramyxoviruses, poxvirus, retroviruses, and rhabdovirus have been reported to utilize both modes of disseminations (Gross and Thoma-Kress, 2016; Sattentau, 2008; Singh et al, 2016; Zhong et al, 2013). In the present study, we have demonstrated that cell-free preparations of the prototypic arenavirus LCMV were unable to infect human pDC CAL-1 cells.…”
Section: Discussionmentioning
confidence: 99%